2004
DOI: 10.1001/archpedi.158.3.217
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Herbal Preparation Containing Echinacea, Propolis, and Vitamin C in Preventing Respiratory Tract Infections in Children

Abstract: Objective: To evaluate the effectiveness and safety of a preparation containing echinacea, propolis, and vitamin C in the prevention of respiratory tract infections in children during a 12-week winter period.Design: Randomized, double-blind, placebo-controlled study.Subjects: Four hundred thirty children, aged 1 to 5 years, were randomized to an herbal extract preparation (n=215) or a placebo elixir (n = 215).Intervention: Administration of an herbal preparation (Chizukit) containing 50 mg/mL of echinacea, 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
0
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(124 citation statements)
references
References 29 publications
3
96
0
6
Order By: Relevance
“…A single recent trial indicated that an herbal preparation containing Echinacea, propolis, and vitamin C prevented the development of upper respiratory infections in children between the ages of 1 and 5 years. 166 Bronchiolitis was not specifically studied.…”
Section: Evidence Profile 10a: Secondhand Smokementioning
confidence: 99%
See 1 more Smart Citation
“…A single recent trial indicated that an herbal preparation containing Echinacea, propolis, and vitamin C prevented the development of upper respiratory infections in children between the ages of 1 and 5 years. 166 Bronchiolitis was not specifically studied.…”
Section: Evidence Profile 10a: Secondhand Smokementioning
confidence: 99%
“…A single recent trial indicated that an herbal preparation containing Echinacea, propolis, and vitamin C prevented the development of upper respiratory infections in children between the ages of 1 and 5 years. 166 Bronchiolitis was not specifically studied.To date, there are no studies that conclusively show a beneficial effect of alternative therapies used for the treatment of bronchiolitis. Recent interest in the use of CAM has led to research efforts to investigate its efficacy.…”
mentioning
confidence: 99%
“…Several new trials of echinacea preparations in the prevention of the common cold have been completed since the Cochrane review, but most have not shown beneficial effects for echinacea preparations compared with placebo on main outcome measures (Melchart et al 1998;Grimm & Mu¨ller 1999;Turner et al 2000;Cohen et al 2004;Sperber et al 2004).…”
Section: Prophylaxis a Cochrane Systematic Review Included 16mentioning
confidence: 99%
“…, propolis 50 mg mL À1 and vitamin C 10 mg mL À1 in children (Cohen et al 2004). In this randomized, double-blind study, 430 children, aged 1 to 5 years, received 5 mL of the preparation (7.5 mL for children aged 4 to 5 years), or placebo, twice daily for 12 weeks over a winter period.…”
mentioning
confidence: 99%
“…Treatment with Echinacea was associated with increased risk of rash compared with placebo group (Taylor et al, 2003). In other study treatment with extract of Echinacea, vitamin C and propolis reduced significantly number and duration of illness episodes in children when compared with placebo treated group (Cohen et al, 2004). Several meta-analysis were performed with great heterogeneity of trials and results suggest that Echinacea extracts might have beneficial effect in the early treatment of common colds, but the there was insufficient evidence to suggest an effect on prevention (Gilles et al, 2000 Linde et al, 2006 Shah et al, 2007.…”
Section: Wwwintechopencommentioning
confidence: 83%